Analisis Komunikasi Organisasi Terhadap Kepuasan Kerja Karyawan Departemen Komunikasi Korporat PT Pindad - Salma Dhiba Rahma Fauzia Ahlan Sudinah; I Gusti Agung Alit Suryawati (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
Organizational communication is a fundamental element that influences the effectiveness of work coordination and employee satisfaction, particularly in large organizations with complex hierarchical structures. This study aims to analyze the state of organizational communication within the Corporate Communications Department of the Corporate Secretary Division at PT Pindad by examining employees’ job satisfaction levels through the lens of organizational communication, as well as to provide recommendations and an evaluation of organizational communication. This study employs a descriptive qualitative approach using data collection techniques such as semi-structured interviews, non-participant observation, and document analysis. Informants were selected through purposive sampling, involving eight active employees from three sub-departments. Data analysis utilized the Miles & Huberman interactive model. The results indicate that communication patterns within this department are hybrid in nature. The barriers identified include incomplete information, differences in interpretation between units, and delays in message delivery. All informants stated that clear, open communication supported by feedback from superiors significantly contributes to motivation and job satisfaction. This study concludes that the effectiveness of organizational communication is closely related to employee job satisfaction, attendance, and productivity.